Bridging the Digital Gap: Evaluating Mobile JKN E-Service Quality at Cisaga Health Center - Devi Fitriani; Endah Mustika Ramdani (Trescode Green Organization, 2025)
The digitalization of public healthcare services in Indonesia, marked by the introduction of the Mobile JKN application, aims to streamline administrative processes and reduce facility congestion. However, a significant